Association after linkage analysis indicates that homozygosity for the 46C→T polymorphism in the F12 gene is a genetic risk factor for venous thrombosis - Tirado, Isabel; Soria, José Manuel; Mateo, José; Oliver, Artur; Souto, Juan Carlos; Santamaria, Amparo; Felices, Rosa; Borrell, Montserrat; Fontcuberta, Jordi (Thrombosis and Haemostasis, 2004)
In a family-based study called GAIT (Genetic Analysis of Idiopathic Thrombophilia) that included a genome-wide scan we demonstrated that a polymorphism (46C→T) in the F12 locus jointly influences variability of plasma (Factor XII) FXII levels and susceptibility to thrombotic disease. It then became germane to determine the prevalence of the 46C→T polymorphism and its relative risk of thrombotic disease. We followed up evidence for genetic linkage with a case-control study, including 250 unrelated consecutive Spanish patients suffering from venous thrombotic disease and 250 Spanish subjects matched for sex and age as a controls. We measured FXII levels and genotyped the 46C→T polymorphism, as well as a number of classical risk factors for thrombotic disease. We confirmed that individuals with different genotypes for this polymorphism showed significant differences in their FXII levels. Most importantly, the mutated T allele in the homozygous state (genotype T/T) was associated with an increased risk of thrombosis (adjusted OR of 4.82; 95% CI 1.5-15.6), suggesting that the polymorphism itself is an independent risk factor for venous thromboembolism. This study confirms that the 46C→T polymorphism is a genetic risk factor for venous thrombosis in the Spanish population. In addition, our results confirm that a genome-wide scan coupled with a classical case-control association study is an extremely valuable approach to identify DNA variants that affect complex diseases.
Keywords: Thrombosis; genetics; risk factors; complex disease